Capacitance Meter with AT89C2051 - Lim Un Tung, Lauw; Budikartono, Mettasari; Tjahyadi, Oentung (Jurnal Teknik Elektro, 2001)
Measuring capacitor%5C%27s capacitance sometimes cannot be done on simple multi-meter. These meters are not equipped with the capacitance meter function found on expensive multi-meter. With the advancing technology in IC integration%2C many micro-controller vendors have provided %5C%22on-chip timer%2Fcounter%5C%22 %28like ATMEL%29%2C that will cut cost on producing a simple capacitance meter. Capacitance is measured by pulse width that is constructed from a multi-vibrator. The ATMEL AT89C2051%5C%27s %5C%22on- chip timer%2Fcounter%5C%22 is used to measure%2C and calculated pulse width%2C then result is shown on a seven segments display. A simple prototype based on the AT89C2051 is able to measure capacitor ranging from 1nF to 470uF. Abstract in Bahasa Indonesia : Tidak semua multimeter mempunyai kemampuan untuk mengukur kapasitas kapasitor. Pada umumnya kemampuan ini hanya terdapat pada multimeter yang mahal harganya. Kapasitas suatu kapasitor dapat diperoleh dengan cara mengukur lebar pulsa yang dihasilkan oleh suatu multivibrator di mana kapasitor tersebut dihubungkan. Dengan mendayagunakan fungsi timer%2Fcounter yang terdapat pada mikrokontroler ATMEL 89C2051%2C lebar pulsa tersebut dapat diukur dan ditampilkan. Pada percobaan telah dapat diukur kapasitor antara 1nF hingga 470uF. Capacitance+Meter%2C+Multi-vibrator%2C+on-chip+timer%2Fcounter